Theoretical and Empirical Evaluation of a Competitive Energy Rebate Program - Chi L. Ta (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Rebates that reward economic agents if they meet a minimum conservation threshold are a popular policy to encourage energy conservation. However, most threshold-based rebates are structured such that they do not encourage reduction beyond the threshold. In this paper, I show theoretically that programs with the additional feature that households compete to win rebates can effectively encourage further conservation among those who can meet the threshold reduction. The theory also identifies factors that determine the effectiveness of the program. I then exploit a unique confidential dataset of monthly residential electricity use with over 45 million observations to estimate the overall effect of a Vietnamese electricity rebate program with this competitive element. Next, I empirically test the model's predictions. I find that the program reduces electricity consumption by 18%, nearly double the threshold level of 10%. Interestingly, the program's effect persists for at least twelve months after it ends, which has important implications for the cost-effectiveness of such interventions.
Keywords: D12; L94; L98; Q48; 330; energy conservation